2022
DOI: 10.3390/nano12122048
|View full text |Cite
|
Sign up to set email alerts
|

Flower-like Composite Material Delivery of Co-Packaged Lenvatinib and Bufalin Prevents the Migration and Invasion of Cholangiocarcinoma

Abstract: The co-delivery of multiple drugs using nanocarriers has been recognized as a promising strategy for cancer treatment to enhance therapeutic efficacy. In this study, a monodisperse mesoporous silica nanoparticle (mSiO2) is prepared and functionalized into high-efficiency loaded Lenvatinib and Bufalin for targeted delivery to Cholangiocarcinoma (CCA). mSiO2 was synthesized on solid silica nanoparticles by oil–water interface method, and highly monodisperse mSiO2 with uniform morphology was obtained. mSiO2 was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…168,169 Most studies on NDDS-LVN have shown that LVN encapsulated in NDDS has similar hematology analysis results, liver and renal function compared with free LVN. 38,41,46,52 Histopathological examination revealed no organ injury or inflammation in NDDS-LVN treated animals compared to free LVN. Interestingly, one study showed lower cytotoxicity of LVN in NDDS at equal concentrations.…”
Section: Reducing Toxicitymentioning
confidence: 88%
“…168,169 Most studies on NDDS-LVN have shown that LVN encapsulated in NDDS has similar hematology analysis results, liver and renal function compared with free LVN. 38,41,46,52 Histopathological examination revealed no organ injury or inflammation in NDDS-LVN treated animals compared to free LVN. Interestingly, one study showed lower cytotoxicity of LVN in NDDS at equal concentrations.…”
Section: Reducing Toxicitymentioning
confidence: 88%
“…The formation of nano-carriers is an effective way to improve the therapeutic effect of bufalin. Several studies have taken advantage of nano-drug delivery systems to target delivery of bufalin for enhance its antitumor therapy and attenuate toxicity, such as platelet membrane biomimetic nanoparticle, liposomes, polymeric prodrug, bovine serum albumin nanoparticle, monodisperse mesoporous silica nanoparticle, metal-organic frameworks(MOFs) and so on (Tian et al 2014;Ning et al 2022;Zeng et al 2021;Hu et al 2012;Wen et al 2017;Ettlinger et al 2022). Zeng et al designed pH-sensitive and redox-responsive folic acid-modified MOFs as drug carriers of bufalin (FA-MOF/Buf ), which could improve water solubility and stability, higher intracellular uptake, and enhanced antitumor effect of bufalin in breast cancer (Zeng et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Zeng et al designed pH-sensitive and redox-responsive folic acid-modified MOFs as drug carriers of bufalin (FA-MOF/Buf ), which could improve water solubility and stability, higher intracellular uptake, and enhanced antitumor effect of bufalin in breast cancer (Zeng et al 2021). Ning et al prepared a monodisperse mesoporous silica nanoparticle to load lenvatinib and bufalin for targeted delivery to cholangiocarcinoma, which indicated a superior therapeutic effect than free drugs (Ning et al 2022). Compared with previously reported nano-drug delivery systems, VES-CSO/TPGS-RGD MMs are easier to prepare and more multifunctional.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we detect the hemolysis rate Cy-HMPBs and Cy-HMPBs/CH The results indicated that the hemolysis rate of all samples was lower than 1%, confirming the bio-safety of our therapeutic strategy (Figure 3H). 54 We then evaluated the photothermal capacity of Cy-HMPBs/CH.…”
Section: Synthesis and Characterizations Of Chmentioning
confidence: 99%